Basic Principles of the Oversight Functions of the House of Representatives on Legislative Functions in Indonesia - Indriani, Santi (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Legislative products have caused public disapproval, so a judicial review has to be submitted to the Constitutional Court (MK). Therefore, it is necessary to analyze the basic principles of the DPR's oversight function of the legislative function in Indonesia. This research aims to examines the basic principles of the duties and powers of the DPR in the oversight function of the legislative function. This research is qualitative research using secondary data. The literature study method was used in collecting data in this study. The data analysis was done using data reduction, displaying, and verification. The study results show that applying the basic principles of the DPR's oversight function to the legislative function in Indonesia is a way or an attempt to see whether the legislative function is carried out according to plan. Oversight by the DPR in forming laws is a preventive measure, such as efforts to prevent irregularities, mistakes, and confusion. The basic principle of the DPR's oversight function of the legislative function contains democratic values, the value of balance, the value of truth, and the value of expediency, which is reflected in the principle of people's sovereignty, the principle of legal certainty, and the principle of justice.